MAINTAINING ENTERPRISE SOFTWARE APPLICATIONS. - Mookerjee, Radha (Communications of the ACM, 2005)
The article focuses on the maintenance of enterprise software applications. Software maintenance is a widely studied area in the information systems literature. Nowadays, a software application is rarely designed to operate as a standalone system, but must interact with other software applications. While the push for creating integrated enterprise applications has profound implications for the practice of new software development, this trend has important consequences for software maintenance as well. In today's world of integrated applications, maintenance practice must not only encompass the maintenance of a single system, but also take into account how any maintenance done on an application impacts other applications. Operational aspects of software maintenance deal with the timing and scope of maintenance activities so as to reduce the total cost of maintaining a group of interdependent systems. The architectural perspective describes steps that can be taken during system development to ease the burden of maintaining a set of integrated applications.